A multi-model based adaptive reconfiguration control scheme for an electro-hydraulic position servo system - Zhang, Zhao; Yang, Zhong; Liu, Shuchang; Chen, Shuang; Zhang, Xiaokai (Zielona Góra: Uniwersytet Zielonogórski)
Reliability and safety of an electro-hydraulic position servo system (EHPSS) can be greatly reduced for potential sensor and actuator faults. This paper proposes a novel reconfiguration control (RC) scheme that combines multi-model and adaptive control to compensate for the adverse effects. Such a design includes several fixed models, one adaptive model, and one reinitialized adaptive model.
Keywords: fault tolerant control; electro-hydraulic position servo system; multiple models; adaptive control; reconfiguration control